enhanced TMJ arthrocentesis for disc displacement without reduction: efficacy of vacuum-assisted technique versus conventional approach: TMJ ARTHROCENTESIS FOR DISC DISPLACEMENT WITHOUT REDUCTION - Grossmann, Eduardo; Poluha, Rodrigo (Headache Medicine, 2024)
-